Serum Albumin and C-reactive protein Ratio as Predictors of Mortality in Critically Ill Children: A Prospective Observational Study at A Tertiary Care Centre - Golhar, Sandeep Tulsidas; Sebastian, Raina; Denge, Abhishek D; Nandikoppa, Parameshappa N; Nayak, Abinash; Khwaja, Sadullah (Journal of Neonatal Surgery, 2025)
Introduction: Critically ill children admitted to Pediatric Intensive Care Units (PICU) have a high risk of mortality.Various prognostic scoring systems have been devised and validated in PICU. However, their applicability is precluded by the lack of resources, expensive laboratory parameters and unavailability of real time test results. There is a need to identify a simple, rapid, and readily accessible biomarker to predict prognosis of critically ill children at admission to the PICU. Methods: We aimed to predict mortality in critically ill children using ratio of C-reactive protein [CRP] and serum albumin levels. Prospective observational study was conducted in children [aged 1month to 12 years, of either sex], admitted to PICU.Serum albumin, CRP were measured to calculate the ratio and mortality was predicted using Receiver operating characteristic (ROC) curves. Result: Among 116 study subjects, 41(35.34%) had respiratory system disorders, 23(19.83%) had CNS disorders, followed by 19 (16.38%) of sepsis. We observed a mortality of 18.1% among children studied, while 81.9% of children survived. Conclusion: The CRP/Albumin ratio among non survivors was significantly greater as compared to survivors (15.3 vs 5.3, p-0.000).